Performing Darna the role of entertainment press in spectacularizing Darna actresses - Brillon, Cherish Aileen A. (2021)
Access online through this link: https://www.plarideljournal.org/article/performing-darna-the-role-of-entertainment-press-in-spectacularizing-darna-actresses
Keywords: Darna (Fictional character); Superheroes; Celebrities